Ability mediation effects in the relationship between human resource practices and service quality - Babaei, Davood; Rahimian, Hamid; Ahmad, Aminah; Omar, Zoharah; Idris, Khairuddin (College of Farabi, University of Tehran, 2015)
In this study, the relationships between Human Resource Practices (HRPs), firm performance (service quality), and the mediation effects of employees’ abilities were examined. To assess the relationships between variables, before evaluating the fitted structural model, the measurement model was defined to verify that the measurement variables used to reflect the unobserved constructs do so in a reliable manner. The Structural Equation Modelling (SEM) was utilized to test the fitness of the model and to provide evidence of discriminate validity through chi-square difference tests. Data were collected from a sample of 179 branches of two banks in Tehran, Iran. Analysis with the bootstrapping method showed that employees’ abilities mediated the relationship between performance appraisal and service quality. Furthermore, the result of this article showed training practices had an indirect significant relationship with service quality through employees’ abilities. Overall, the findings of the current study provided insights into the role of HRPs and employees’ abilities in firm performance. Furthermore, it becomes important for organizations to build strategic practices in terms of training, career development, participation, and performance appraisal.